KONFIGURASI POLA SPASIAL LANSKAP DI SEKITAR KAWASAN HUTAN LINDUNG GUNUNG NONA AMBON - Aryanto Boreel; Lydia R. Parera; Nitha N. Farneubun (JURNAL HUTAN PULAU-PULAU KECIL, 2023)
This research aims to observe land use changes and analyze the configuration of spatial landscape patterns around the protected forest area of Gunung Nona Ambon in 2014 - 2020. This research was conducted with two analyses. The first stage is identifying land cover/land use changes in the last 6 years (2014 - 2020) through spatial analysis (overlay). The second stage is to analyze the configuration of spatial patterns of forest landscapes using the spatial metrics method. The results showed that during the 6-year period (2014-2020), the forest class experienced significant changes. Changes in forest land use around the HLGN area dominantly occurred in the settlement class, followed by shrubs and open land classes of 5.62%, 5.37% and 3.38% respectively of the existing forest area in the study area. The configuration of spatial patterns of settlement land such as density and continuity showed that the spatial patterns were increasingly concentrated and dense and the areas were physically connected to each other. Similarly, the fragmentation indicator shows that the settlement land pattern is increasingly massive and clustered.